Effects of IV Fluids in Dogs and Cats With Kidney Failure - Langston, Cathy; Gordon, Daniel (Frontiers in Veterinary Science, 2021)
Intravenous fluid therapy has long been the mainstay of treatment of kidney disease, including acute kidney injury and uremic crisis associated with chronic kidney disease. Careful management of fluid dose is critical, as animals with kidney disease may have marked derangements in their ability to regulate fluid homeostasis and acid-base status. Understanding of the physiology of renal fluid handling is necessary, along with repeated attention to parameters of fluid status, electrolytes, and acid-base balance, to achieve optimal hydration status and avoid further damage or decrease in function from dehydration or overhydration.